Effects of temperature on PO and resistivity of ScAlN film. (October 2015) - Yang, YX.; Li, XM.; Zhou, D.; Yang, CT.; Feng, F.; Yang, JS.; Hu, QJ.
<x content-type="archive" xml:space="preserve">Abstract</x> Sc doped AlN (ScAlN) films were prepared by dc reactive magnetron sputtering. The crystal quality, surface topography, cross-sectional view and the resistivity of ScAlN thin films grown on Si (100) substrates at various substrate temperatures from room temperature to 650°C have been investigated. Results show that the temperature has a significant effect on the properties of ScAlN thin films. According to the research, the crystal quality of ScAlN film first increases and then decreases, reaching the best crystalline state at 600°C. The best surface morphology and cross-sectional view of ScAlN thin film was obtained at 600°C. The resistivity first increased to a maximum value of 3·36 × 1012 Ω·cm and then decreased with the temperature increasing.